Keputusan Memilih Di Kalangan 'Silent Majority' Dan 'Vocal Minority' Mahasiswa Pengguna Media Sosial Pada Pilpres 2024 - Hutasoit, Joshua Alfen Pratama (Jurnal Mahardika Adiwidia, 2025)
This research aims to determine the voting decisions of students belonging to the Silent Majority and analyze the differences in media preferences and choices between the Silent Majority and Vocal Minority. The theoretical framework used in this study is the Spiral of Silence theory. The research employs an associative quantitative method with non-probability and purposive sampling techniques, selecting 111 respondents from Pertamina University students (class of 2020-2024). Hypothesis testing results show significant differences between the Silent Majority and Vocal Minority regarding their presidential candidate preferences and social media usage. The findings highlight that social media sentiment does not always reflect real-world election outcomes